An effect of electrokinetics phenomena on nonlinear wave propagation in bubbly liquids - Panahov, Geylani; Abbasov, Eldar; Bakhtiyarov, S.; Museibli, Parviz (Zielona Góra: Uniwersytet Zielonogórski)
A study of nonlinear waves in liquid-gas mixtures with the consideration of internal effects is an important problem of both the fundamental and the applied fluid mechanics. Investigation of nonlinear waves in the gas-liquid mixtures with allowance for internal effects is an important task of both fundamental and applied fluid mechanics.
Keywords: nonlinear waves; bubbly liquids; electrokinetic phenomena; perturbation; electric potential